Beyond Political Correctness : Toward the inclusive university - Weir, Lorna, 1952-; Richer, Stephen (Book collections on Project MUSE., 1995)
Part One explores the history and social organization of the discourse, with the accent on Canadian material. The essays explore what the term has signified to different groups and to what ends they have used it. This section moves from an overview of political-correctness discourse to its explicit manifestation within universities in debates concerning academic ideals. Part Two looks at the classroom, a major site for building the inclusive university. Here, contributors explore feminist and anti-racist teaching and the limitations to such teaching imposed by the economic and political contexts of contemporary universities.